Synthesis and Cytotoxicity of Thiophene, Thieno[2,3-C]Pyrazole, Thieno[2,3-D]Pyrimidine and Pyridine Derivatives Derived from 2-Acetylfuran - Mohamed, Abeer A; Abouzied, Amr S; Hamed, Faten I (International Journal of Chemistry and Materials Research, 2017)
This work deals with the synthesis and cytotoxicity of some heterocyclic compounds starting from 2-acetylfuran. The title compound was used for the synthesis of thiophene derivative 3 through its reaction with elemental sulfur and ethyl cyanoacetate. Compound 3 was used for the synthesis of thiophene, thieno[2,3-c]pyrazole, thieno[2,3-d]pyrimidine and pyridine derivatives through its reaction with different reagents. The newly synthesized compounds were screened through three cancer cell lines. Compound 13b showed the highest potency among the synthesized compounds.